International trade and retail market performance and structure: Theory and empirical evidence - Philipp Meinen; Horst Raff (Deutsche Bundesbank, 2018)
Based on a theoretical model featuring heterogeneous retailers that may source globally and operate as chains, we derive a number of hypotheses that link trade integration to retail firm performance and to the structure of retail markets. We empirically test these predictions using Danish microdata for the period 1999 to 2008. We find that importing retailers are larger, more profitable, and have a higher propensity to have multiple shops than domestically sourcing firms. While this is partly due to self-selection, we also present evidence for improved performance caused by firms' importing activities. Moreover, we find that retail imports are associated with a higher exit probability of small retailers and greater local retail market concentration. Overall, we obtain support for the model's predictions and argue that the observed adjustments may imply additional gains from trade absent from models lacking a distribution sector.
Keywords: F12; L11; 330; international trade; consumer goods; retailing; retail chains